A full Brazilian or all natural: understanding the influences on young women’s decision to remove their pubic hair - Patricia Obst; Katherine White; Ebony Matthews (BMC Women's Health, 2019)
Abstract Background Research indicates that young women are being exposed to increasing pressures to remove pubic hair from their bodies, which has the potential for both negative physical and psychological consequences. Women’s personal choice and reasoning for partaking in pubic hair removal is influenced by broader social influences; however, there is little theory-based research drawing from established decision-making models investigating the underlying processes that lead young women to engage in pubic hair removal practices. Based on the Theory of Planned Behaviour, it was hypothesised that 1) attitude, subjective norm, and perceived behavioural control would predict intention to remove pubic hair; 2) additional variables (prototype similarity and favourability) from the Prototype Willingness Model would significantly predict intention to remove pubic hair; 3) feminist values would significantly predict decreased intention to remove pubic hair; and 4) intention and perceived behavioural control would predict future self-reported removal of pubic hair. Method The current study included a sample of 270 young women (17–25 years old), who completed an online survey and a follow up survey 4 weeks later (N = 96). Results Attitudes, perceived behavioural control, and similarity to prototypical pubic hair removers were significant predictors of intention to remove pubic hair. Intention was significantly positively associated and feminist values were significantly negatively associated with actual pubic hair removal. Conclusions These findings align with Theory of Planned Behaviour propositions. Furthermore, the expansion of the model highlights how broader social images impact on young women when deciding whether to engage in a behaviour that is intimately associated with their body image.